2001
DOI: 10.1128/iai.69.9.5412-5416.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Protective Potential of the Immune Response toTaenia soliumParamyosin in a Murine Model of Cysticercosis

Abstract: Paramyosin has been proposed as a vaccine candidate in schistosomiasis and filariasis. However, limited information is available about its protective potential against cysticercosis and the immune response it induces. Immunization of mice with recombinant full-length paramyosin of Taenia solium (TPmy) results in about a 52% reduction in parasite burden after a subsequent challenge by intraperitoneal inoculation of Taenia crassiceps cysticerci. Immunization assays using recombinant fragments of TPmy, correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…This coincides with previous studies on the vaccination/immunization of paramyosins from other helminth parasites [11,27,38,39]. Due to its high level of immunogenicity, paramyosin has been proposed as potential vaccine candidate in a number of helminthiases, including schistosomiasis [20,21,28,39,40], filariasis [22,23] and cysticercosis [27,29]. We also found that rats vaccinated with rCsPmy (100 mg/rat) and challenged with 100 metacercariae of C. sinensis showed reduced worm burden (11.6-20.6%) compared to control rats (our unpublished data).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This coincides with previous studies on the vaccination/immunization of paramyosins from other helminth parasites [11,27,38,39]. Due to its high level of immunogenicity, paramyosin has been proposed as potential vaccine candidate in a number of helminthiases, including schistosomiasis [20,21,28,39,40], filariasis [22,23] and cysticercosis [27,29]. We also found that rats vaccinated with rCsPmy (100 mg/rat) and challenged with 100 metacercariae of C. sinensis showed reduced worm burden (11.6-20.6%) compared to control rats (our unpublished data).…”
Section: Discussionsupporting
confidence: 71%
“…These results suggested that paramyosin of helminth parasites are multifunctional proteins acting not only as structural protein in muscle layers to control their contraction physiologically, but also as an immunoregulatory molecule interacting with the host immune system. In addition, immunogenic properties of paramyosins of helminth parasites make them potential vaccine candidates [11,[20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Paramyosin is considered a vaccine candidate against schistosomiasis mansoni (42), schistosomiasis japonicum (24,46), filariasis (29,38), and cysticercosis (57). It acts as one of the major schistosome immunogens during infection with S. mansoni in mice (27) and humans (47).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic vaccines are particularly appealing for applications in developing countries as they can be inexpensive to produce and store (5). In the present study, we evaluated the use of genetic immunization with the amino-terminal fragment of T. solium paramyosin (VW2-1), which was previously shown to be protective (15), as an alternative strategy for vaccination in the murine model of Taenia crassiceps cysticercosis.…”
mentioning
confidence: 99%
“…A strong effort is currently being directed toward the development of an effective vaccine against porcine cysticercosis. A number of strategies have been proposed, including the use of parasite crude extracts (9,17), recombinant proteins (2,3,15), synthetic peptides (4), phage display (8), and genetic immunization (10,18). Genetic vaccines are particularly appealing for applications in developing countries as they can be inexpensive to produce and store (5).…”
mentioning
confidence: 99%